Customary land and the claim of matrimonial property - Supaat D.I.; Abidah Abdul Ghafar; Yaakob A.; Shah H.A.R.; Muda F.S.; Norfadhilah Mohamad Ali; Shukor S.A.; Arif Fahmi Md Yusof; Suraiya Osman (American Scientific Publishers, 2024)
Indexed by Scopus/ERA